Effect of Green Practices on Organizational Performance: An Empirical Study - M. Gaikwad, Lokpriya; K. Sunnapwar, Vivek (Journal of Basic & Applied Sciences, 2021)
Global manufacturing businesses have contributed to energy and resource consumption, pollution. Along with governmental legislation, social and market pressure that growing as awareness about environmental issues increases. To tackle such problems the study focuses on the analysis of the direct consequence of Green Manufacturing (GM) practices on operational performance in the manufacturing industry. A model for evaluating the effect of GM is developed taking into consideration as a fundamental variable that affects the causal relationship between GM practices and operational performance. A structural equation model was proposed and investigated across the manufacturing industry in India. A structured survey questionnaire was used to gather empirical data from 400 Indian companies. A total of 203 usable responses were obtained giving a response rate of 53%. The data was analyzed using SPSS- AMOS software. The results revealed that GM practices directly and positively affected operational performance. The results indicated that the structural equation model remained invariant across the Industry. The implementation of Green practices in manufacturing has been recognized as a mean to improve economic and environmental performance that increases competitiveness and urge innovation. The study provides further evidence to managers and practitioners on the effect of GM practices on operational performance in developing countries like India.